Buckling of Arteries With Noncircular Cross Sections: Theory and Finite Element Simulations - Seddighi, Yasamin; Han, Hai-Chao (Frontiers in Physiology, 2021)
The stability of blood vessel is essential for maintaining the normal arterial function and loss of stability may result in blood vessel tortuosity. Our previous theoretical models of artery buckling were developed for circular vessel models, but arteries often demonstrate geometric variations such as elliptic and eccentric cross sections. The objective of this study was to establish the theoretical foundation for non-circular blood vessels and simulate the bent (i.e. lateral) buckling behavior of arteries with elliptic and eccentric cross sections using finite element analysis. Generalized buckling equation for non-circular vessels was derived and finite element analysis was conducted to simulate the artery buckling behavior under lumen pressure and axial tension. The arterial wall was modeled as a thick-walled cylinder with hyper-elastic anisotropic and homogeneous material. Our results demonstrated that oval or eccentric cross section increases the critical buckling pressure of arteries and having both ovalness and eccentricity would further enhance the effect. We conclude that variations of the cross-sectional shape affect the critical pressure of arteries. These results improve our understanding of the mechanical stability of arteries.